MI-5. Volume 02 [videorecording (DVD)] - Nalluri, Bharat; Macfadyen, Matthew, 1974-; Hawes, Keeley, 1976-; Oyelowo, David; Firth, Peter, 1953-; Simon, Hugh (BBC Video ; Distributed by Warner Home Video, 2004)
The threat to national security increases and the need to thwart the activities of terrorists operating within the UK becomes more urgent.